RESPONSE OF THE CORE AND SHIELD RODS OF TIME-DOMAIN REFLECTOMETRY PROBE TO TRANSVERSE SOIL-WATER CONTENT HETEROGENEITY - Mojid M.A.; Cho H. (My University, 2002)
The effect of the speed of a time-domain reflectometry (TDR) pulse through the core rod and the shield rod(s) of TDR probes on the dielectric constant and water content of a soil with heterogeneous water content distribution in the transverse direction to the probe length was investigated. Soil samples were prepared using sands of two different water contents, which were kept side by side to get transverse heterogeneous water content distribution. The dielectric constant and water content of these samples (here after denoted by #TDR and θTDR, respectively) were measured by TDR. The expected dielectric constants of the samples, #g, were calculated using the equation of Topp et al. (1980) from the volumetric soil-water contents, θg, measured gravimetrically assuming that this equation was applicable to our soil. The TDR pulse traveled faster through the probe rod inserted in the dry sand due to its low dielectric constant than through the probe rod inserted in the wet sand. So, early reflection of the pulse occurred in the dry sand, which shortened the travel path of the pulse and caused underestimation of the dielectric constant and soil-water content. The degree of this underestimation was higher when the core rod of the probe was in dry sand than when was this same rod in wet sand. Although TDR measurements were apparently controlled by the dry part of the sample, θTDR was always higher than the water content of the dry sand, θdry, in the sample. TDR thus could measure neither the average dielectric constant and soil-water content of the sample nor it measured those for the dry part or for the wet part of the sample when soil-water distribution was heterogeneous in the transverse direction of the probe rods.
Keywords: TIME-DOMAIN REFLECTOMETRY PROBE; CORE AND SHIELD RODS; TRANSVERSE HETEROGENEOUS; SOIL-WATER CONTENT